Eribulin in advanced liposarcoma and leiomyosarcoma. Issue 8 (3rd August 2017) - Setola, Elisabetta; Noujaim, Jonathan; Benson, Charlotte; Chawla, Sant; Palmerini, Emanuela; Jones, Robin L.
ABSTRACT: Introduction : The heterogeneity of soft tissue sarcomas (STS) presents a formidable management challenge. Consequently, one of the main research goals is to define specific tailored therapy for each histological subtype and to develop a more personalised approach to treatment. The standard first line chemotherapy for advanced STS is doxorubicin, with or without ifosfamide, however, a number of different drugs are emerging as active therapies beyond first-line. Areas covered : Eribulin has recently been approved for advanced liposarcoma, after an anthracycline-containing regimen, demonstrating an overall survival (OS) advantage in liposarcoma and leiomyosarcoma in a randomised Phase III clinical trial. In this manuscript, an overview of the efficacy and safety of eribulin in STS is presented, highlighting different clinical outcomes between histological subtypes and comparing data with other effective drugs used in the treatment of sarcomas. The potential mechanisms of action of eribulin are also described, including its activity as potent microtubule-destabilizing anticancer agent, which has other antitumor biological effects. Expert commentary : Eribulin is highly effective in some STS populations and also has an acceptable toxicity profile. Further studies are required to better understand the precise mechanism of action of this agent and potential role in combination schedules.